RESEARCH ON THE APPLICATION OF QFORM SOFTWARE FOR ROLLING SMALL-SIZED CONICAL BILLETS - Berdiyev Darob Muratovich,; Saydumarov Botir Muradovich,; Tashmatov Ravshan Kobilovich,; Xasanov Kamoliddin Akmal o‘g‘li,; Mo‘minov Afzalsho Oljabay o‘g‘li, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The development of a rolling process technology regime using simulation with the QForm software package for forming the base of a cutting tooth used in mineral extraction from 35XGSA steel billets produced by JSC “Uzmetkombinat” is considered one of the urgent problems. The rolling process is a metal forming process in which the material is deformed by passing it between rolling rolls, and it is widely used in industry. Conical workpieces (billets) are often required for products such as bushings, pins, and conical adapters. In traditional experimental production, the development of such parts requires significant time and resources. Therefore, preliminary verification and optimization of the technology through computer simulation is an effective solution.